An Unusual Case of ACLF : First Report from Bangladesh - Al Mamun, Ayub; Al-Mahtab, Mamun; Islam, Abu Saleh Mohammad Sadequl; Abedin, Mohammad Forhad; Saha, Dulal Chandra; Akbar, Sheikh Mohammad Fazle; Rahman, Salimur (Journal of Medicine, 2014)
Autoimmune hepatitis is often unrecognized and under-diagnosed, especially in our part. Acute on chronic liver failure (ACLF) on the other hand is a newly recognized disease entity describing patients who develop acute liver failure on the background of pre-existing chronic liver disease. Methods: We present an elderly lady who presented to us with history of episodic fever and jaundice over a period of two years. Results: Although initially diagnosed as a case of idiopathic thrombocytopenic pupura (ITP), on further investigation she was finally diagnosed as ACLF (hepatitis B virus induced acute liver failure on autoimmune hepatitis induced cirrhosis of liver). DOI: http://dx.doi.org/10.3329/jom.v14i2.19674 J Medicine 2013, 14(2): 192-194